Temporomandibular manifestation in patients with Ehlers-Danlos syndrome: a systematic reviewEspañol - Español, Español (2023)
Introduction: Ehlers-Danlos Syndrome (EDS) consists of a group of diseases that imply a disorder among individual connective tissue due to an altered collagen production. Fibrocartilaginous structures, support ligaments, disc and retrodiscal from the temporomandibular joint are composed primarily of collagen. Objective: Identify TMJ manifestations in patients with different types of EDS. Materials and Methods: a systematic review of the literature was performed on PubMed, Scopus and Web of Science databases. Observational studies and case series reports published either in Spanish or not Spanish were included up until January 2023. Results: 12 articles met the inclusion criteria. The prevalence of temporomandibular disorders varies from 26.6% to 100%, being EDSh the most reported subtype, whereas disc displacement with or without reduction and joint hypermobility were the most reported joint disorders. Conclusion: Temporomandibular pathologies are common in patients with EDS, especially in those with the EDSh subtype.